Physicochemical, microbiological and sensory profiles of fermented milk containing probiotic strains isolated from kefir - Kakisu, Emiliano Javier (2011)
A two-strain starter culture containing Lactobacillus plantarum CIDCA 83114, a potential probiotic strain isolated from kefir grains, and Streptococcus thermophilus CIDCA 321 was tested for the preparation of a fermented milk product. Kluyveromyces marxianus CIDCA 8154, a yeast with immunomodulatory properties was included to formulate a three-strain starter culture. Supernatants of enterohaemorragic Escherichia coli, shiga-toxin–producing strain, along with a two-strain or a three-strain starter culture were included in the medium of Vero-cell surface cultures. The results demonstrated that these combinations of microorganisms antagonize the cytopathic action of shiga toxins. The cell concentration of Lb. plantarum did not decrease during fermentation, indicating that the viability of this strain was not affected by low pH, nor did the number of viable bacteria change during 21 days of storage in either fermented products. The number of viable yeasts increases during fermentation and storage. Trained assessors analyzed the general acceptability of fresh fermented milks and considered both acceptable. The milk fermented with the two-strain starter culture was considered acceptable after two week of storage, while the product fermented with the three-strain starter culture remained acceptable for less than one week. The main changes in sensory attributes detected by the trained panel were in sour taste, milky taste and also in fermented attributes. The correlation between different sensory attributes and acceptability indicated that the panel was positively influenced by milky attributes (taste, odour, and flavour) as well as the intensity of flavour. In conclusion, the two-strain starter culture would be the more promising alternative for inclusion of that potential probiotic lactobacillus in a fermented milk product.